Eksplorasi Peran Kolaboratif dan Tantangan Guru Pendamping Khusus (Shadow Teacher) dalam Mendukung Pembelajaran Siswa ABK di SMP Negeri 7 Salatiga - Sekar Kusuma Kasih; Dimas Ardy Aditya; Hesti Aries Tina (Lembag, 2025)
This study aims to describe the collaborative role and challenges faced by Special Assistant Teachers (GPK) or shadow teachers in supporting the learning of students with Special Needs (ABK) at SMPN 7 Salatiga. The method used in this study is a literature study, by reviewing various literature on inclusive education, the role of GPK, exploratory learning, and collaboration between teachers and parents. The results of the study indicate that GPK has an important role in academic assistance, behavioral management, social-emotional facilitation, and bridging communication between teachers, students, and parents. However, the implementation of inclusive education still faces several obstacles, such as limited facilities and infrastructure, low understanding and support from parents, lack of training for teachers, and variations in student abilities that require differentiated learning. This study emphasizes the importance of strengthening collaboration between stakeholders, optimizing facilities, and improving teacher competency so that inclusive education can run more effectively and support the development of students with Special Needs.